Names, diversity and innovation - Anna Kremer (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2021)
Diversity of a country is often measured by the amount and spread of nationalities that live there. But also within a country, regions vary in their traditions and culture. Cultural homogeneity within communities is mixed up by (internal) migration, that, like international migration, increases diversity of a place. In a novel approach I therefore look at diversity in German municipality associations measured by different family names and investigate the effect it has on the number of generated patents. I show that cultural diversity and openness of a place affect its economic performance positively in terms of innovation also when referring to intra-country differences.
urn:nbn:de:bsz:14-qucosa2-749819
Keywords: O31; R12; Z10; J61; O1; 330; cultural diversity; innovation; openness; phonebook; patents; local level; Germany; kulturelle Diversität; Innovation; Offenheit; Telefonbuch; Patente; lokal; Deutschland